Open access, responsibility and the “platformization” of academic publishing - Tabarés, Raúl (NOvation — Critical Studies of Innovation, 2022)
Digitalization was supposed to be a transformation force for the academic publishing sector, but it has reinforced the oligopoly of for-profit academic publishers. Open access (OA) was also meant to counterbalance this situation, but after a decade of efforts it seems that it has not achieved their goals. This essay explores how the combination of digitalization and OA have contributed to reinforce the lock-in effects exerted in the sector by digital platforms operated by for-profit academic publishers. I also explore alternative paths for the development of OA with the theoretical lenses that provide responsible innovation, putting social emphasis at the politics and values that lie at the heart of academia. I argue that exploitation, appropriation of labor and quantification metrics widely present in this social domain must be counterbalanced with different actions that do not focus alone in making freely available scientific articles for citizens.